Silver Nanoparticles Functionalized With Antimicrobial Polypeptides: Benefits and Possible Pitfalls of a Novel Anti-infective Tool - Zharkova, Maria S.; Golubeva, Olga Yu.; Orlov, Dmitriy S.; Vladimirova, Elizaveta V.; Dmitriev, Alexander V.; Tossi, Alessandro; Shamova, Olga V. (Frontiers in Microbiology, 2021)
Silver nanoparticles (AgNPs) and antimicrobial peptides or proteins (AMPs/APs) are both considered promising platforms for the development of novel therapeutic agents effective against the growing number of drug-resistant pathogens. The observed synergy of their antibacterial activity suggested the prospect of introducing antimicrobial peptides or small antimicrobial proteins into the gelatinized coating of AgNPs. Conjugates with protegrin-1, indolicidin, protamine, histones and lysozyme were comparatively tested for their antibacterial properties and compared with unconjugated nanoparticles and antimicrobial polypeptides alone. Their toxic effects were similarly tested against both normal eukaryotic cells (human erythrocytes, peripheral blood mononuclear cells, neutrophils, dermal fibroblasts) and tumor cells (human erythromyeloid leukemia K562 and human histiocytic lymphoma U937 cell lines). The AMPs/APs retained their ability to enhance the antibacterial activity of AgNPs against both Gram-positive and Gram-negative bacteria, including drug-resistant strains, when conjugated to the AgNP surface. The small, membranolytic protegrin-1 was the most efficient, suggesting that a short, rigid structure is not a limiting factor despite the constraints imposed by binding to the nanoparticle. Some of the conjugated AMPs/APs clearly affected the ability of nanoparticle to permeabilize the outer membrane of E. coli, but none of the conjugated AgNPs acquired the capacity to permeabilize its cytoplasmic membrane, regardless of the membranolytic potency of the bound polypeptide. Low hemolytic activity was also found for all AgNP-AMP/AP conjugates, regardless of the hemolytic activity of the free polypeptides, making conjugation a promising strategy not only to enhance their antimicrobial potential, but also to effectively reduce the toxicity of membranolytic AMPs. The observation that metabolic processes and O2 consumption in bacteria were efficiently inhibited by all forms of AgNPs is the most likely explanation for their rapid and bactericidal action. AMP-dependent properties in the activity pattern of various conjugates toward eukaryotic cells suggest that immunomodulatory, wound-healing, and other effects of the polypeptides are at least partially transferred to the nanoparticles, so that functionalization of AgNPs may have effects beyond just modulation of direct antibacterial activity. In addition, some conjugated nanoparticles are selectively toxic to tumor cells. However, caution is required as not all modulatory effects are necessarily beneficial to normal host cells.